Nitrogen Supply Affects Yield and Grain Filling of Maize by Regulating Starch Metabolizing Enzyme Activities and Endogenous Hormone Contents - Yue, Kai; Li, Lingling; Xie, Junhong; Liu, Yaoquan; Xie, Jianhui; Anwar, Sumera; Fudjoe, Setor Kwami (Frontiers in Plant Science, 2022)
This research aimed to examine the effect of nitrogen (N) application rate and time on yield, grain filling, starch metabolizing enzymes, and hormones of maize based on a long-term field experiment which initiated in 2012. The total N fertilizer dose [(0 (N0), 100 (N1), 200 (N2), and 300 (N3) kg N ha-1) was split into two (T1, one-third at sowing and two-thirds at the six-leaf stage) or three (T2, one-third each at sowing, six-leaf, and eleven-leaf stage) times application. The results showed that the highest yield was obtained under N3T2, N2T1, and N3T2 in 2018, 2019, and 2020, which was 222.49, 185.31, and 194.00 % than that of N0 in each year, respectively. N2 and N3 significantly increased the yield through enhancing ears ha-1, grains per plant, and 100-grains weight, however, N2 and N3 didn’t show significant difference on yield and above yield components. Additionally, N application time didn’t significantly change yield under same N rate. N0 limited the activities of starch metabolizing enzymes, resulting in insufficient accumulation of sucrose and starch. The contents of indole-3-acetic acid, cytokinin, abscisic acid, and gibberellin were decreased under N0 during grain filling. The average grain filling rate and maximum grain filling rate (Gmax) and grain weight increment achieving Gmax increased under N2 and N3, and the grain filling parameters were positively correlated with 100-grains weight. In conclusion, 200 kg N ha-1 with one-third application at sowing and two-thirds application at the six-leaf stage is a suitable N supply way to improve starch metabolizing enzymes, regulate hormone content, and enhance grain filling rates, and thus increasing the maize yield in the semi-arid Loess Plateau of China.